The relationship between credit policy and firms’ profitability: empirical evidence from Indian pharmaceutical sector - Najib H.S. Farhan; Mosab I. Tabash; Mohammad Yameen (Investment Management & Financial Innovations, 2020)
Credit policy plays a vital role in the operational efficiency of credit departments as it reduces the ambiguity of credit departments’ functions by giving clear guidelines and instructions. It also reduces the loan default and speeds up accounts receivable turnover. This paper seeks to evaluate the effect of credit policy on the profitability of pharmaceutical firms listed on the Bombay Stock Exchange (BSE), using a balanced panel data of 82 pharmaceutical firms from 2008 to 2017. The number of days’ collection period and the number of days’ payable deferral period are chosen for measuring firms’ credit policy, while return on assets (ROA) is used for measuring firms’ profitability. It is found that the number of days’ collection period and the number of days’ payable deferral period have a negative and significant effect on the profitability of the pharmaceutical firms, while the control variables leverage, firm size, and age negatively impact the profitability of pharmaceutical firms. Financial managers in pharmaceutical companies should reduce the number of days’ collection period and increase the number of days’ deferral period to reduce the risk of bad debts. Furthermore, they should conduct a credit analysis to evaluate potential clients as it prevents bad debts.